2021
DOI: 10.1093/dnares/dsab014
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes and DNA methylomes in apomictic cells delineate nucellar embryogenesis initiation in citrus

Abstract: Citrus nucellar poly-embryony (NPE) is a mode of sporophytic apomixis (SA) that asexual embryos formed in the seed through adventitious embryogenesis from the somatic nucellar cells. NPE allows clonal propagation of rootstocks, but it impedes citrus cross breeding. To understand the cellular processes involved in NPE initiation, we profiled the transcriptomes and DNA methylomes in laser microdissection (LMD) captured citrus apomictic cells. In apomictic cells, ribosome biogenesis and protein degradation were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Analysis of FhRWP and its homologs across Citrinae revealed a striking pattern of MITE insertions in the 5’ promoter regions of these genes. Apomictic accessions in Citrus and Fortunella contain two or three MITE insertions in the RWP promoter, respectively, while sexually reproducing Citrinae individuals lack MITE insertion [ 6 , 53 ]. These MITE insertions correlate with RWP gene expression levels in the nucellus of apomicts [ 36 ] and act as apparent binding targets of the transcriptional regulator FhARID , which may mediate gene expression and embryogenic induction.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of FhRWP and its homologs across Citrinae revealed a striking pattern of MITE insertions in the 5’ promoter regions of these genes. Apomictic accessions in Citrus and Fortunella contain two or three MITE insertions in the RWP promoter, respectively, while sexually reproducing Citrinae individuals lack MITE insertion [ 6 , 53 ]. These MITE insertions correlate with RWP gene expression levels in the nucellus of apomicts [ 36 ] and act as apparent binding targets of the transcriptional regulator FhARID , which may mediate gene expression and embryogenic induction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the impact of epigenetic perturbations on apomixis, at least two loci were reported to be hypomethylated in apomictic female organs compared to sexual gametophytes of the grass Cenchrus ciliaris [36], suggesting that DNA methylation loss might be more severe during development of apomictic embryo sacs than gametogenesis. Nonetheless, methylome dynamics of adventitious embryos are reminiscent to the one observed during early development of sexual embryos [24], with early nucellarderived embryos showing global CHH hypomethylation compared to surrounding maternal tissues [37].…”
mentioning
confidence: 95%
“…Another mechanism influencing alteration of DNA methylation patterns should also be considered. Recently, a DNA methylome analysis revealed hypermethylation in the promoter of CitRWP in polyembryonic citrus, which contains a MITE insertion, while hypomethylation was detected in the promoter of CitRWP in monoembryonic citrus without a MITE insertion [ 89 ]. This result suggests that the MITE insertion may be related to the hypermethylation of CitRWP , which might activate gene transcription and further enable cells in the ovules of polyembryonic citrus to switch to an apomictic pathway.…”
Section: Miniature Inverted-repeat Transposable Element Transposons M...mentioning
confidence: 99%
“…Transcriptome comparison of apomictic Boechera , Hieracium , and Hypericum with related sexual lines revealed changes in siRNA synthesis and RNA-directed DNA methylation (RdDM)-related gene expression [ 90 92 ]. DNA methylation analysis showed that the overall methylation level of gametophyte-apomictic C. ciliaris [ 93 ] and sporophyte-apomictic citrus [ 89 ] was lower than that of sexually reproducing plants, suggesting that hypomethylation is related to apomictic reproduction, while in the gametophyte-apomictic Paspalum treatment with the DNA methylation inhibitor 5-azacytidine significantly reduced parthenogenesis frequency, suggesting that a high DNA methylation level may maintain apomictic reproduction [ 94 ].…”
Section: Epigenetic Regulation Of Apomixismentioning
confidence: 99%
See 1 more Smart Citation